Communicative Action in COVID-19 Prevention: Does Religiosity Play a Role? - Chin, Ying Shin (Animo Repository, 2021)
Coronavirus disease (COVID-19) has presented the world with a major challenge in curbing infection. Information is important for public awareness of the pandemic and its prevention as part of the problem-solving efforts. Grounded on the situational theory of problem solving (STOPS), this study extends the theory by adding religiosity, an important factor that affects health-related behaviors, to examine its role as an antecedent to the situational perceptions that motivate people to take communicative action in preventing COVID-19, and to investigate the factors that lead to precautionary behavior in response to the pandemic. Based on the online survey responses from 371 respondents, the findings of the current study suggest that religiosity predicts problem recognition and constraint recognition, which further lead to communicative action in problem solving. Religiosity, however, does not predict involvement recognition. Religiosity and situational motivation were also found to be significantly related to precautionary behavior. The outcomes can serve as a guideline for the Malaysian Health Promotion Board in information dissemination during a pandemic.